ГРУПОВЕ ПОРУШЕННЯ ГРОМАДСЬКОГО ПОРЯДКУ ТА ХУЛІГАНСТВО: ПРОБЛЕМИ РОЗМЕЖУВАННЯ - Олійничук, Роман (Актуальні проблеми правознавства, 2017)
Олійничук Р. Групове порушення громадського порядку та хуліганство: проблеми розмежування. Розглянуто групове порушення громадського порядку та хуліганство як кримінально карані діяння проти громадського порядку та моральності. Проаналізовано погляди науковців на правові категорії, які стосуються розмежування даних злочинів. Висвітлено наукові позиції щодо відмінностей між хуліганством і груповим порушенням громадського порядку. Обґрунтовано дискусійність окремих тверджень науковців щодо теми дослідження. Зроблено авторський висновок про відмінність складів досліджуваних злочинів. Олийнычук Р. Групповое нарушение общественного порядка и хулиганство: проблемы разграничения. Рассмотрены групповое нарушение общественного порядка и хулиганство как уголовно наказуемые деяния против общественного порядка и нравственности. Проанализированы взгляды ученых на правовые категории, которые касаются разграничения данных преступлений. Рассмотрены научные позиции о различиях между хулиганством и групповым нарушением общественного порядка. Обосновано дискуссионность отдельных утверждений ученых по теме исследования. Сделано авторский вывод о различии составов исследуемых преступлений. Oliynychuk R.Group breach of public order and hooliganism: the problems of differentiation. The group breach of public order and hooliganism as punishable acts against public order and morality were examined in the article. The views of scientists on legal categories relating to differentiation of these crimes were analyzed. The scientific positions on the differences between hooliganism and group breach of public order were considered. The contradictory of some statements of scientists on the research topic was grounded. The results of the research is analyses of the current criminal legislation and scientific views on the legal categories relating to differentiation of group breach of public order and hooliganism as well as grounding the author’s conclusion about the difference between these crimes. There was made a conclusion concerning differences which should distinguish between the group breach of public order and the hooliganism, provided by Articles 293 and 296 of the Criminal Code of Ukraine, which are the following: 1. The signs of the objective side (in the nature and content of criminal acts, place and circumstances of the crime). 2. The construction of crimes (art. 293 Criminal Code of Ukraine – material and art. 296 of the Criminal Code of Ukraine – formal). 3. The number of participants (in group breach of public order actions are committed by group of persons, while hooliganism – actions can be committed by either alone or group of persons). 4. The signs of the subject (the subject of hooliganism can be a person under 14 years old and group breach of public order – under 16 years old). 5. The signs of subjective side (Art.293 of the Criminal Code of Ukraine provides both direct and indirect intents, and art. 296 of the Criminal Code of Ukraine – only direct; and hooligan motives of the crime, which is characteristic for hooliganism). The ordinary of the research is reasoning of differences which should use for differentiation of group breach of the public order and the hooliganism. The practical value of the research is that the results of comparative legal studies on the differentiation of group breach of public order and hooliganism can be used in practice to correct qualification of the crimes.